Case report: Successful radical surgery following complete pathological remission of advanced HCC with Tislelizumab/Lenvatinib plus TACE - Xie, Yong; Lyu, Tianshi; Zou, Yinghua; Wang, Jian (Frontiers in Oncology, 2024)
The combination therapy of Tislelizumab plus Lenvatinib has recently emerged as the new standard of care for unresectable hepatocellular carcinoma (HCC). This treatment has demonstrated a significant reduction in tumor burden, raising the possibility of conversion therapy. However, the full safety and efficacy of this combination in real-world settings are not yet fully understood. We recently reported the case of a 36-year-old man with initially unresectable massive HCC, for whom radical surgery (RS) was contraindicated. After receiving Tislelizumab/Lenvatinib plus transarterial chemoembolization (TACE), the patient achieved complete pathological remission and subsequently underwent RS. The patient did not experience postoperative severe complications, and there was no recurrence during the follow-up period. Tislelizumab/Lenvatinib plus TACE therapy may lead to a complete pathological response in advanced HCC. Nevertheless, the safety of prolonged treatment needs to be assessed.